Brittle-stars (Echinodermata: Ophiuroidea) from the continental shelf and upper slope of the Colombian Caribbean - Borrero-Pérez, G. H. (2008)
An annotated brittle star list (Echinodermata: Ophiuroidea) collected by bottom trawling between 20 and 520 m depth during the INVEMAR-MACROFAUNA campaigns (1998-2001) along the continental shelf and upper slope of the Colombian Caribbean is presented. A total of 58 species were identified: 41 genera, 13 families and 2 orders, in which 35 species are new records for the Colombian Caribbean (28 are also new for the continental part of the Caribbean Sea). General and detailed figures are provided. Rev. Biol. Trop. 56 (Suppl. 3): 169-204. Epub 2009 January 05.